Glasba in staranje - Lunežnik, Vita (Muzikološki zbornik, 2018)
The article focuses on the benefits of music for older adults in retirement homes. Relevant literature was studied to investigate the theoretical and sociocultural context. Furthermore, participatory action research was conducted in the Ptuj retirement home. The findings indicate that the music programme has substantial personal and social value for the residents.
Keywords: akcijske raziskave; andragogika; glasbeno izobraževanje; izobraževanje starejših; participatorni pristop